Luz Saúde buyout: Equity valuation - Carvalho, João Diogo (2018)
Luz Saúde is on the main players on Portuguese private healthcare business, owning 9% of the market share. It became the first Portuguese healthcare listed company in 2014 with an initial price of €3.20 per share; in the same year, the insurance company Fidelidade, bought 96% of the company and became the majority shareholder at that time. Currently, the capital is mainly divided by Fosun (49%) and Fidelidade (49.7%). In 2018 it was decided by both to buyout the rest of the dispersed shares, offering €5.71 per share. Therefore, the aim of this thesis is to value the equity side of Luz Saúde and reach a fair price per share and to conclude over the reasonableness of the price offered by Fosun and Fidelidade to the minority investors. As the purpose of the thesis is to value only the equity side, the valuation methodology followed the free cash-flow to the equity approach and relative valuation based on comparable companies. Dividend discount model was not used since Luz Saúde never paid any dividend and it is not expectable that it will do so.